PENGARUH LAMA SIMPAN SEMEN DENGAN PENGENCER TRIS AMINOMETHAN KUNING TELUR PADA SUHU RUANG TERHADAP KUALITAS SPERMATOZOA KAMBING BOER - M Fajar Agustian; M Nur Ihsan; Nurul Isnaini (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2014)
This study was conducted from May to June 2014 at Sumber Sekar Labolatory of Animal Husbandry Faculty, University of Brawijaya, Malang. The purpose of the study was to find out quality of semen Boer goat in room temperature with different storage duration. The result showed that storage treatment of semen with yolk tris aminhomethan diluents had highly signicant defferen as (P<0.01) on individual motility, viability and abnormality of semen. The conclusion of this result was optimal storage time was 240 minutes in room temperature with 53.50±2.42% of individual motility, 61.29±3.15% of viability and 15.15±2.42% of abnormality. Keyword: semen, Boar goat, tris aminomethane yolk, storage